First measurements of g factors in the even Kr isotopes - Mertzimekis, T. J.; Benczer-Koller, N.; Holden, J.; Jakob, G.; Kumbartzki, G.; Speidel, K.-H.; Ernst, R.; Macchiavelli, A.; McMahan, M.; Phair, L.; Maier-Komor, P.; A. Pakou; et al. (Phys. Rev. C, 2001)
The g factors of the 2+1 and 4+1 states in 78,80,82,84,86Kr have been measured for tne first time, using Coulomb excitation of isotopic Kr beams and the transient field technique. The measured g factors of 2+1 states in 78.80.82Kr are well described, in both magnitude and progression with neutron number, by the IBA-II model. Whereas the lighter isotopes show a dominant collective structure with g factor values close to Z/A, the large g(2-1) = 1.12(14) value of 86Kr, with its closed N = 50 shell, is unequivocally dominated by specific proton configurations. The g factor of the 2+1 state in 84Kr, with two holes in the Ig9/2 neutron orbit, reflects both proton and neutron components in the wave function. In addition, the lifetimes of several 2+1 and 4+1 states were remeasured by the Doppler shift attenuation method, yielding values which, in some cases, differ from those in the literature.